2022
DOI: 10.3389/fimmu.2022.982772
|View full text |Cite
|
Sign up to set email alerts
|

Inborn errors of immunity and related microbiome

Abstract: Inborn errors of immunity (IEI) are characterized by diverse clinical manifestations that are dominated by atypical, recurrent, chronic, or severe infectious or non-infectious features, including autoimmunity, lymphoproliferative disease, granulomas, and/or malignancy, which contribute substantially to morbidity and mortality. Some data suggest a correlation between clinical manifestations of IEI and altered gut microbiota. Many IEI display microbial dysbiosis resulting from the proliferation of pro-inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 143 publications
0
0
0
Order By: Relevance
“…At taxonomic levels, in CVID, we observed the relative expansion of the genus Streptococcus and the decreasing abundance of the families Prevotellaceae, Fusobacteriaceae, Veillonellaceae, Campylobacteraceae , and Flavobacteriaceae , the most abundant phyla of healthy lung microbiomes ( 6 ). A similar depletion is observed in respiratory conditions such as pneumonia, COPD, and in smokers ( 32 37 ), together with the overgrowth of P.aeruginosa , S.pneumoniae, S.aureus, H. Influenza , and Burkholderia cepacia complex ( 11 ), leading to increased inflammation and lung injury ( 29 ). In our CVID cohort, respiratory acute infections have been positively related to the expansion of Haemophilus and Anoxybacillus , which has been previously associated with lung function worsening in Idiopathic Pulmonary Fibrosis ( 35 ) and exacerbations in asthma and COPD ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…At taxonomic levels, in CVID, we observed the relative expansion of the genus Streptococcus and the decreasing abundance of the families Prevotellaceae, Fusobacteriaceae, Veillonellaceae, Campylobacteraceae , and Flavobacteriaceae , the most abundant phyla of healthy lung microbiomes ( 6 ). A similar depletion is observed in respiratory conditions such as pneumonia, COPD, and in smokers ( 32 37 ), together with the overgrowth of P.aeruginosa , S.pneumoniae, S.aureus, H. Influenza , and Burkholderia cepacia complex ( 11 ), leading to increased inflammation and lung injury ( 29 ). In our CVID cohort, respiratory acute infections have been positively related to the expansion of Haemophilus and Anoxybacillus , which has been previously associated with lung function worsening in Idiopathic Pulmonary Fibrosis ( 35 ) and exacerbations in asthma and COPD ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 71%
“…Secretory IgA is crucial to engendering robust host-microbial symbiosis, allowing colonization in mucosal niches through the exclusion of exogenous competitors ( 10 ). In patients with Inborn Errors of Immunity (IEI), adaptive or innate immune system defects led to gastrointestinal, respiratory, and cutaneous involvement frequently associated with dysbiosis ( 11 , 12 ). Specifically, changes in gut microbiota have been described in patients with common variable immunodeficiency (CVID) due to defects in mucosal immunity and increased microbial translocation ( 13 , 14 ), resulting in inflammation and immune dysregulation ( 13 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…The intestinal microbiota comprises bacteria (Lactobacillaceae, Lactococcus sp., Enterococcaceae, Bacteroidesthetaiotaomicron, Bacteroidesfragilis, and Bacteroidesovatus), viruses, protozoa, and fungi (Candida, Saccharomyces, Malassezia, and Cladosporium) [27]. Patients with inborn errors of immunity have abnormal interactions between their microbiome and immune system [28].…”
Section: Intestinal Microbiotamentioning
confidence: 99%
“…It was demonstrated that low microbial diversity post-HSCT leads to the emergence of Escherichia sp., Staphylococcus sp., and Enterococcus sp. [6,27,65]. Lane et al reported changes in gut microbiome composition after HSCT in cases with X-linked SCID and RAG deficiency [66,67].…”
Section: Scid Is a Monogenic Disorder Due To A Defect In T- B- And Nk...mentioning
confidence: 99%